Combined use of clinical pre-test probability and D-dimer test in the diagnosis of preoperative deep venous thrombosis in colorectal cancer patients - Stender, Mogens Tornby; Frøkjær, Jens Brøndum; Nielsen, Tina Sandie Hagedorn; Larsen, Torben Bjerregaard; Lundbye-Christensen, Søren; Elbrønd, Henrik; Thorlacius-Ussing, Ole (Thrombosis and Haemostasis, 2008)
The preoperative prevalence of deep venous thrombosis (DVT) in patients with colorectal cancer may be as high as 8%. In order to minimize the risk of pulmonary embolism, it is important to rule out preoperative DVT. A large study has confirmed that a negative D-dimer test in combination with a low clinical pre-test probability (PTP) can be safely used to rule out the tentative diagnosis of DVT in cancer patients. However, the accuracy in colorectal cancer patients is uncertain. This study assessed the diagnostic accuracy of a quantitative D-dimer assay in combination with the PTP score in ruling out preoperative DVT in colorectal cancer patients admitted for surgery. Preoperative D-dimer test and compression ultrasonography for DVT were performed in 193 consecutive patients with newly diagnosed colorectal cancer. Diagnostic accuracy indices of the D-dimer test were assessed according to the PTP score. The negative predictive value, positive predictive value, sensitivity and specificity were 99% (95% confidence interval (CI), 95–100%), 17% (95% CI, 9–26), 93% (95% CI, 68–100%) and 61% (95% CI, 53–68%), respectively. In conclusion, the combined use of pre-test probability and D-dimer test may be useful in ruling out preoperative DVT in colorectal cancer patients admitted for surgery.
Keywords: Colorectal cancer; D-dimer; diagnostic accuracy; preoperative; venous thromboembolism